Impact of brackets on smile esthetics: laypersons and orthodontists perception - Seandra Cordeiro de Oliveira; Rachel D'Aurea Furquim; Adilson Luiz Ramos (Dental Press Editora, 2012)
OBJECTIVE: This study evaluated the influence of orthodontic appliances on smile esthetics assessed by lay adolescents, lay adults and orthodontists. METHODS: A facial photograph of a smiling young woman was used under the following conditions: With metal orthodontic brackets ligated by different elastic ligature colors (green, red and gray), with ceramic bracket brackets (transparent elastic ligature) and without brackets, totaling five 15 x 20 cm pictures. For the photograph assessment, 16 lay adolescents, 16 lay adults and 16 orthodontists were randomly selected. The photographs were randomly arranged in an album, followed by a visual analog scale (VAS) for the scores registration. Scores in both evaluations of each group of evaluators (adolescents, adults and orthodontists) were submitted to error analysis by WILCOXON test and multiple comparison among groups performed by Kruskal - Wallis at 5% significance. RESULTS: Orthodontists, adults and adolescents agreed in their opinions, although the orthodontists gave lower scores in their assessments. It could be observed that ceramic brackets were more acceptable concerning the smile esthetics, whereas the metal brackets received the lowest scores. CONCLUSION: Orthodontists, adults and even adolescents seem to prefer esthetic solutions during orthodontic treatment. OBJETIVO: esse estudo analisou a influência dos aparelhos ortodônticos na estética do sorriso em avaliação por adolescentes, adultos e ortodontistas. MÉTODOS: foram utilizadas fotografias faciais do sorriso de uma jovem mulher, usando-se as seguintes combinações: aparelho ortodôntico de metal com ligaduras de diferentes cores (verde, vermelho e cinza); aparelho ortodôntico cerâmico (ligadura transparente); e sem aparelho - resultando em cinco fotografias de 15x20cm. Para a avaliação das fotografias, 16 adolescentes leigos, 16 adultos leigos e 16 ortodontistas foram selecionados de forma randômica. As fotografias foram aleatoriamente organizadas em um álbum, acompanhadas de uma escala visual analógica (EVA) para o registro das notas. As notas das duas avaliações de cada grupo (adolescentes, adultos e ortodontistas) foram submetidas à análise de erro (teste pareado de Wilcoxon) e comparação múltipla de grupos pelo teste de Kruskal-Wallis com significância de 5%. RESULTADOS: ortodontistas, adultos e adolescentes concordaram em suas opiniões, porém, os ortodontistas deram notas menores em suas avaliações. Pôde ser observado que os braquetes cerâmicos foram mais aceitos, considerando-se a estética do sorriso, uma vez que os braquetes metálicos tiveram as menores notas. CONCLUSÃO: ortodontistas, adultos e adolescentes parecem preferir soluções estéticas durante o tratamento ortodôntico.